(3GQJTGa GdVQH ef dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s
(3ChdgG (B:s
(3Ce HYO aEf Yde GdfMh UYH GdeQGe eSJYU Ydi GdCagGe hMUQJg ai LedJjf GdChd ai CMcGe Gdcde bHd GdJQcjH s
(3BNQgG (B:s
(3hESJYeGd GdUaI ESJYeGd GdLGeO eVGaI ddYOO ef KdGKI Edi YTQI bO EQJTaJ GdCfGed Ydi VQH Gdef GdJYH s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdCdaGX HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs